Implementasi Eliminasi TBC dalam Mewujudkan Lingkungan Sehat di Kecamatan Cibeber Kabupaten Lebak - Stiawati, Titi; Maisaroh, Ima; Ifdal Dikri, Muhammad Januar (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2025)
This study discusses the implementation of the Tuberculosis (TB) Elimination policy in creating a healthy environment in Cibeber District, Lebak Regency, which has the highest number of TB cases compared to other districts. The high incidence rate is driven by low public education, strong social stigma, and concerning socio-economic conditions. The research used a qualitative method with a case study approach. Data analysis was conducted using the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing. Data was collected through in-depth interviews with health workers, village officials, and community members, direct observation, and documentation studies of activity reports and epidemiological data. Specifically, this research was analyzed using Donald Van Meter and Carl Van Horn's Public Policy Implementation Theory, focusing on six variables: (1) Policy Standards and Objectives, (2) Resources, (3) Characteristics of Implementing Agencies, (4) Dispositions of Implementors, (5) Inter-Organizational Communication, and (6) External Environment (economic, social, political). The results show that the implementation of the TB elimination program has not been optimal. Based on the theoretical framework, the findings reveal main obstacles in the Resources variable (limitations in human resources, facilities and infrastructure, and uneven drug distribution), the Dispositions of Implementors variable (less than optimal), and the External Environment variable in the form of socio-economic conditions and low public awareness. Although Inter-Organizational Communication ran quite well, unstable social and economic factors remained the main obstacles to creating a healthy and TB-free environment in Cibeber District.